2010
DOI: 10.1519/jsc.0b013e3181aff28b
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Secretory Immunoglobulin A Response of Elite Speed Skaters During a Competition Period

Abstract: We aimed to determine the responses of salivary secretory immunoglobulin A (SIgA) and the incidence of upper respiratory tract infections (URTI) symptoms among elite speed skaters during an actual competition period. The subjects were 8 international-class elite speed skaters. Saliva samples were obtained 3, 2, and 1 days before the race, the day of the race, and 1 day after the race. Salivary secretory immunoglobulin A concentration was measured by enzyme immunoassay, and SIgA secretion rate was calculated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In the present study, an acute bout of high-intensity exercise resulted in a 31.6% decrease in the secretion rate of SIgA. This finding is consistent with earlier studies where the secretion rate of SIgA levels was decreased 29.3% after an ultra-endurance race 36 and 33% after a skating race 23 . Other tests of high-intensity exercise also produced decreased secretion rates of SIgA such as a 23.3% decrease after a rugby game 18 and decreases after repeated Wingate tests of 27.8% in women 9 and 38.8% in men 6 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, an acute bout of high-intensity exercise resulted in a 31.6% decrease in the secretion rate of SIgA. This finding is consistent with earlier studies where the secretion rate of SIgA levels was decreased 29.3% after an ultra-endurance race 36 and 33% after a skating race 23 . Other tests of high-intensity exercise also produced decreased secretion rates of SIgA such as a 23.3% decrease after a rugby game 18 and decreases after repeated Wingate tests of 27.8% in women 9 and 38.8% in men 6 .…”
Section: Discussionsupporting
confidence: 93%
“…With respect to physical exercise, cortisol and testosterone levels in saliva were found to correlate well to blood levels and in combination with immunoglobulin A abundance have served as markers for stress responses in context of various sports activities . However, a full proteome profiling analysis combined with an untargeted analysis of salivary small molecules in individuals subjected to physical exercise has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effect of exercise, some studies have shown that acute bout of exercise, including incremental all-out treadmill exercises, may decrease salivary IgA in young athletes (37)(38)(39)(40)(41)(42)(43)(44)(45)(46), whereas other studies have found no association between SIgA and exercise (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Very few studies reported, instead, an increase of SIgA (63)(64)(65)(66).…”
Section: Acute Bouts Of Exercise Salivary Secretory Immunoglobulin-a (Siga) and The Effect Of Exercisementioning
confidence: 99%